Directional diffusivity changes in the optic nerve and optic radiation in optic neuritis - Li, M (The British Institute of Radiology., 2011)
OBJECTIVE: Optic neuritis (ON) is defined as an inflammation of the optic nerve and provides a useful model for studying the effects of inflammatory demyelination of white matter. The aim of this study was to assess the diffusion changes in both the optic nerve and optic radiation in patients with acute and chronic ON using diffusion tensor (DT) MRI. METHODS: 33 patients with idiopathic demyelinating optic neuritis (IDON) and 33 gender- and age-matched healthy controls were examined with DT-MRI and with T(1) and T(2) weighted MRI. RESULTS: Compared with controls, both first-episode and recurrent patients with IDON in the acute stage showed significantly increased radial diffusivity (λ(⊥)) and decreased mean fractional anisotropy (FA) in the affected nerves. Reduced FA, increased λ(⊥), mean diffusivity (MD) and axial diffusivity (λ(∥)) were determined in patients with subacute IDON. We found no significant difference in the directional diffusivity of optic radiation in patients whose disease had lasted less than 1 year compared with healthy controls. However, significant changes in the FA and λ(⊥) of the optic radiation were detected in patients with disease duration of more than 1 year. CONCLUSION: These results show the great potential and capacity of DT-MRI measures as useful biomarkers and indicators for the evaluation of myelin injury in the visual pathway.